Experimental study on hybrid solar system fitted with special heat exchanger and flat reflectors. (2017) - Palaskar, V.N.; Deshmukh, S.P.
The hybrid photovoltaic/thermal (PV/T) solar water systems are not cost economic because of low concentration ratios, less combined efficiencies and non-standardisation of heat exchanger surfaces. The simple and effective technique used to increase performance of hybrid system must enhance available solar radiation on its surface for its working period. This can be accomplished by fitting flat reflectors to module side. This paper analyses performance of spiral flow heat exchanger of hybrid system with reflectors fixed to shorter sides of module. The results such as performance efficiencies of photovoltaic, thermal, and combined photovoltaic/thermal are compared for forced and natural circulation of water through heat exchanger of system. At peak PV point, natural flow system worked with combined efficiency of 56.60% and forced flow system worked with marginally high combined efficiency of 57.74%. The results of the study showed that for this system, thermo-siphon method if used can be an ideal solution for generation of electrical power and hot water.